A note on the cost of capital with fixed payout ratios - Ralf Diedrich; Stefan Dierkes; Hans-Christian Gröger (Review of Quantitative Finance and Accounting, 2022)
The insights of Modigliani and Miller (Am Econ Rev 53:433–443, 1963) and Miles and Ezzell (15:719–730, https://doi.org/10.2307/2330405 , 1980) on the cost of capital of firms rank among the most important results in financial theory. The underlying assumptions regarding the financial policy, however, can hardly be reconciled with empirical findings. We investigate the implications of an alternative approach that is characterized by a fixed payout ratio. By introducing additional assumptions about investment opportunities, we find relationships between the cost of equity of levered and unlevered firms. The results contribute to explaining empirical findings and open the possibility to base valuation techniques on realistic and yet practicable assumptions.
Keywords: G11; G32; G35; 330; Cost of capital; Dividend policy; Payout ratio; Financing policy; Capital structure